Slovenia's steps on the European path - Mavčič, Arne (Dignitas (Ljubljana), 2025)
he article discusses the first steps of slovenia on its path toward accession, adaptation, and implementation of the Eu-ropean convention on Human rights and the case law of the European court of Human rights. Although the conven-tion was known under the previous system, its actual part-nership was unattainable in the then political circumstances, as the conditions for membership in the council of Europe were not met and the level of human rights protection re-mained questionable. the former Yugoslavia did submit an application for membership in the council of Europe shortly before its dissolution, but it was never realized. this turning historical period — a time of major social and political chang-es following the decline of soviet influence — encouraged processes of democratization and transformation of values throughout Europe, particularly in its eastern part. For slo-venia, it was a time of exceptional sensitivity due to the war events in the neighbourhood, yet with internal political unityit succeeded in taking a new, democratic path. shortly after independence, slovenia became the first new state in the re-gion to join the Venice commission and to establish partner-ship with the council of Europe, the European convention, and the European court of Human rights. the acceptance of the convention’s values and the court’s case law among the first new or renewed states marked the beginning of a period of adaptation, renewal, and internalization of funda-mental democratic principles throughout slovenian society and the state.
Keywords: democratization; demokratizacija; European Convention on Human Rights; European Court of Human Rights; Evropska konvencija o človekovih pravicah; Evropsko sodišče za človekove pravice; načelo subsidiarnosti; Slovenian Constitutional Court; Slovenija; slovensko ustavno sodišče; subsidiarity principle